2020
DOI: 10.3389/fmicb.2019.03132
|View full text |Cite
|
Sign up to set email alerts
|

Initial Transcriptomic Response and Adaption of Listeria monocytogenes to Desiccation on Food Grade Stainless Steel

Abstract: The foodborne pathogen Listeria monocytogenes survives exposure to a variety of stresses including desiccation in the food industry. Strand-specific RNA sequencing was applied to analyze changes in the transcriptomes of two strains of L. monocytogenes (Lm 568 and Lm 08-5578) during desiccation [15 • C, 43% relative humidity (RH)] on food grade stainless steel surfaces over 48 h to simulate a weekend with no food production. Both strains showed similar survival during desiccation with a 1.8-2 Log CFU/cm 2 reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 120 publications
2
16
0
Order By: Relevance
“…However, deletion of cspA only in the more desiccation-resistant food and outbreak-related L. monocytogenes strains (568 and 08-5578) had no impact on desiccation tolerance, although compared to the parent strains, the mutants were also nonmotile [ 19 ]. Expression of cspA was upregulated in wild-type EGDe, 568 and 08-5578 strains in response to desiccation stress confirming a role for cspA during desiccation survival [ 19 , 92 ]. Therefore, the fact that cspA deletion had no impact on 568 and 08-5578 strains desiccation stress sensitivity is indicative that functional redundancy might exist in these two strains regarding desiccation, which might not exist in EGDe.…”
Section: Role Of Csps In L Monocytogenes Stress Tolerancementioning
confidence: 95%
See 1 more Smart Citation
“…However, deletion of cspA only in the more desiccation-resistant food and outbreak-related L. monocytogenes strains (568 and 08-5578) had no impact on desiccation tolerance, although compared to the parent strains, the mutants were also nonmotile [ 19 ]. Expression of cspA was upregulated in wild-type EGDe, 568 and 08-5578 strains in response to desiccation stress confirming a role for cspA during desiccation survival [ 19 , 92 ]. Therefore, the fact that cspA deletion had no impact on 568 and 08-5578 strains desiccation stress sensitivity is indicative that functional redundancy might exist in these two strains regarding desiccation, which might not exist in EGDe.…”
Section: Role Of Csps In L Monocytogenes Stress Tolerancementioning
confidence: 95%
“…These tolerance phenotypes could also be related to loss or reduction of motility in these mutants. Other studies have suggested that decreased or absence of motility might favor enhanced desiccation tolerance as enormous cellular resources are expanded to build and run the motility apparatus [ 91 , 92 ]. However, deletion of cspA only in the more desiccation-resistant food and outbreak-related L. monocytogenes strains (568 and 08-5578) had no impact on desiccation tolerance, although compared to the parent strains, the mutants were also nonmotile [ 19 ].…”
Section: Role Of Csps In L Monocytogenes Stress Tolerancementioning
confidence: 99%
“…It is intriguing to find out whether drying for 16–24 h used in our study could have enhanced the resistance of Lm to QAC. Transcriptomic analysis of Lm desiccated on stainless steel showed that genes involved in response to other stresses were also upregulated [ 38 ]. Desiccation-treated Salmonella showed enhanced tolerance to multiple disinfectants, such as QAC, ethanol, sodium hypochlorite, hydrogen peroxide, and bile salts [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…When L. monocytogenes was desiccated for short and extended timepoints on steel plates, it was revealed that 16 CDGC genes altered in expression (11 upregulated and five downregulated). Interestingly, both eutV/eutW were downregulated in all five measured timepoints (Kragh and Truelstrup Hansen, 2019). Maintaining food at cold temperatures is another prominent method used for controlling the growth of pathogens and other spoilage organisms.…”
Section: Implications For Survival In Food and Food Production Enviromentioning
confidence: 91%
“…These strains often harbor genes that confer increased tolerance to stresses associated with these habitats, i.e., protection against methods used to control microbial growth in food production operations. The literature strongly suggests that the CDGC may provide survival advantages to L. monocytogenes during exposure to disinfectants, growth inhibitors, desiccation, and during cold temperature (Chan et al, 2008;Fox et al, 2011;Mattila et al, 2012;Tessema et al, 2012;Hingston et al, 2017;Suo et al, 2018;Kragh and Truelstrup Hansen, 2019;Cortes et al, 2020).…”
Section: Implications For Survival In Food and Food Production Enviromentioning
confidence: 99%